Hepatocyte Growth Factor Enhances Vascular Endothelial Growth Factor-Induced Angiogenesis in Vitro and in Vivo - Xin, Xiaohua (American Society for Investigative Pathology, 2001)
Vascular endothelial growth factor (VEGF) is an important mediator of angiogenesis in both physiological and pathological processes. Hepatocyte growth factor (HGF) is a mesenchyme-derived mitogen that also stimulates cell migration, and branching and/or tubular morphogenesis of epithelial and endothelial cells. In the present study, we tested the hypothesis that simultaneous administration of HGF and VEGF would synergistically promote new blood vessel formation. HGF acted in concert with VEGF to promote human endothelial cell survival and tubulogenesis in 3-D type I collagen gels, a response that did not occur with either growth factor alone. The synergistic effects of VEGF and HGF on endothelial survival correlated with greatly augmented mRNA levels for the anti-apoptotic genes Bcl-2 and A1. Co-culture experiments with human neonatal dermal fibroblasts and human umbilical vein endothelial cells demonstrated that neonatal dermal fibroblasts, in combination with VEGF, stimulated human umbilical vein endothelial cells tubulogenesis through the paracrine secretion of HGF. Finally, in vivo experiments demonstrated that the combination of HGF and VEGF increased neovascularization in the rat corneal assay greater than either growth factor alone. We suggest that combination therapy using HGF and VEGF co-administration may provide a more effective strategy to achieve therapeutic angiogenesis.